Developing Countries and Enforcement of Trade Agreements : Why Dispute Settlement is Not Enough - Bown, Chad P.; Bernard M., Hoekman (World Bank, Washington, DC, 2012)
Poor countries are rarely challenged in formal World Trade Organization trade disputes for failing to live up to commitments, reducing the benefits of their participation in international trade agreements. This paper examines the political-economic causes of the failure to challenge poor countries, and discusses the static and dynamic costs and externality implications of this failure. Given the weak incentives to enforce World Trade Organization rules and disciplines against small and poor members, bolstering the transparency function of the World Trade Organization is important for making trade agreements more relevant to trade constituencies in developing countries. Although the paper focuses on the World Trade Organization system, the arguments also apply to reciprocal North-South trade agreements.